Ответы и объяснения

2013-01-18T16:02:37+04:00

1)x^2-5x+6=0

D= (-5)^2-4*1*6=25-24=1

x1=(5+корень из 1)/2=(5+1)/2=6/2=3
x1=(5-корень из 1)/2=(5-1)/2=4/2=2

x^2-5x+6 = (x-3)(x-2)

2)(x^2-4)=0

x^2=4
Т.к. 4>0, то 2 корня

x1=корень из 4   и    x2= -корень из 4

x1=2  и    x2= -2

x^2-4= (x-2)(x+2)

(x-3)(x-2)/(x-2)(x+2)=x-3/x+2

 

 

 

 

 

                  

  • z768
  • середнячок
2013-01-18T16:04:06+04:00

Составить систему:

x^2-5x+6=0

x^2-4 не равно 0

1-ое уравнение: 

D = (-5)^2 - 4*1*6 = 1

X1 = 5 + 1/2*1 = 3

X2 = 5 - 1/2*1 = 2

 

2-ое уравнение:

 (x-2)*(x+2) не равно 0

 X1 не равен 2

 X2 не равен -2

Значит корень уравнения - только 3

Ответ: x = 3